The Impact of Historical Literacy on Youth Political Attitudes in a Post-Communist Society - Kalemi, Ramiola; et al. (European Journal of Social Science Education and Research, 2026)
This study analyzes the impact of knowledge about the communist system in Albania on the political attitudes and social perceptions of young people within a post-communist society. The study relies on a quantitative methodology and is based on data collected through a structured questionnaire administered to 430 young people aged 18-30 years in the Durres region. The questionnaire was implemented and analyzed using statistical techniques such as linear regression and analysis of variance (ANOVA). The findings show that although factors such as age and education do not significantly correlate with the level of historical knowledge, knowledge of communism itself has a positive and significant influence on the development of a critical attitude toward the democratic system. The study emphasizes the importance of historical education and highlights the value of a more structured and critical engagement with the communist past within the educational curriculum in strengthening democratic consciousness among young people.
Keywords: Collective Memory, History Education, Political Socialization, Historical Knowledge, Youth Political Attitudes, Democratic Consciousness.